CATALYTIC SYNTHESIS OF DIVINYL FROM ETHYL ALCOHOL - D. S Abdimurodova; N. I. Fayzullayev (Innovate Conferences, 2025)
In this research work, the dehydrogenation reaction of ethyl alcohol was studied in a flow-type catalytic device at temperatures of 473-573 K and atmospheric pressure. Metals supported on silicon oxide and magnesium, zirconium, and lanthanum oxides activated on SiO2 were used as the catalytic system. The high catalytic activity and productivity of the catalysts were studied at various temperatures and conversion conditions.